Analysis of the Antioxidant and Anticancer Bioactivity of Gamal Plants with Basic In Silico Methods: ANALISIS BIOAKTIVITAS ANTIOKSIDAN DAN ANTIKANKERTANAMAN GAMAL METODE IN SILICO DASAR - Dodi Iskandar (PT. ROCE WISDOM ACEH, 2024)
In silico research has been carried out to analyze the antioxidant and anticancer bioactivity of the Gliricidiasepium plant. The software used includes knapsackfamily, pubchem, chemdraw, swissadme, passonline and MS excel. The result is that all compounds in the Gliricidia sepium plant have antioxidant and anticancer probability values ​​above 0.500. Sepinol has the highest probability value of 0.873 for antioxidant, 0.869 for free radical scavenger, 0.784 for anticarcinogenic and 0.745 for chemopreventive. As for TP53, the strongest expression enhancer is robinetin with a probability value of 0.920.